A One Pot Synthesis of 5, 7-diaryl-1,5-dihydro (or 1, 2, 3, 5-tetrahydro)- pyrano[2, 3-D] pyrimidin-2, 4-diones (or 2-thioxo-4-ones) - Rahman, M Mahbubur; Ahmed, S Mosaddeq; Siddiki, SMA Hakim; Halim, Md Ershad; Akhter, Kawsari; Ahmed, M Giasuddin; Romman, UKR (Dhaka University Journal of Science, 2013)
A number of 5, 7-diaryl-1,5-dihydro (or 1, 2, 3, 5-tetrahydro)- pyrano[2, 3-d] pyrimidin-2, 4-diones (or 2-thioxo-4-ones) (3a-f) have been synthesized in one-step by cyclocondensation of barbituric acid or thiobarbituric acid (1) with arylideneacetophenones (2a-c), in glacial acetic acid in the presence of phosphorous pentoxide. The structures of the compounds 3a-f have been determined by UV, IR, 1H NMR, 13C NMR, mass spectral data and elemental analyses. DOI: http://dx.doi.org/10.3329/dujs.v61i2.17065 Dhaka Univ. J. Sci. 61(2): 167-171, 2013 (July)